2018
DOI: 10.1084/jem.20171704
|View full text |Cite
|
Sign up to set email alerts
|

Bhlhe40 is an essential repressor of IL-10 during Mycobacterium tuberculosis infection

Abstract: The cytokine IL-10 antagonizes pathways that control () infection. Nevertheless, the impact of IL-10 during infection has been difficult to decipher because loss-of-function studies in animal models have yielded only mild phenotypes. We have discovered that the transcription factor basic helix-loop-helix family member e40 (Bhlhe40) is required to repress expression during infection. Loss of Bhlhe40 in mice results in higher expression, higher bacterial burden, and early susceptibility similar to that observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
140
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(156 citation statements)
references
References 59 publications
(95 reference statements)
12
140
4
Order By: Relevance
“…15 In contrast, IL-10 production by pulmonary PMNs was actively repressed during Mycobacterium tuberculosis. 55 In this study, we did not detect an upregulation in IL-10 production by PMNs in response to S. pneumoniae infection in WT mice either in vivo during lung challenge or in vitro in response to direct bacterial infection. Further, we were unable to detect an increase in IL-10 mRNA in PMNs isolated from human donors in response to stimulation with S. pneumoniae.…”
Section: Discussioncontrasting
confidence: 68%
“…15 In contrast, IL-10 production by pulmonary PMNs was actively repressed during Mycobacterium tuberculosis. 55 In this study, we did not detect an upregulation in IL-10 production by PMNs in response to S. pneumoniae infection in WT mice either in vivo during lung challenge or in vitro in response to direct bacterial infection. Further, we were unable to detect an increase in IL-10 mRNA in PMNs isolated from human donors in response to stimulation with S. pneumoniae.…”
Section: Discussioncontrasting
confidence: 68%
“…27 BHLHE40 also play important roles in inflammatory diseases. 28 In autoimmune neuroinflammation, BHLHE40 in Th cells contributes to disease progression. 28 In autoimmune neuroinflammation, BHLHE40 in Th cells contributes to disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…During Mycobacterium tuberculosis infection, BHLHE40 is indispensable to resistance to bacterial infection by repressing IL-10 expression in both T cells and myeloid cells. 28 In autoimmune neuroinflammation, BHLHE40 in Th cells contributes to disease progression. [29][30][31] In colitis model and Toxoplasma gondii infection model, BHLHE40 served as a molecular switch in determining the balance between the inflammatory cytokine IFN-γ and the anti-inflammatory cytokine IL-10 in Th1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…IL‐10, a cytokine with anti‐inflammatory properties, can be produced by many immune cells including macrophages, B cells, natural killer cells, and nearly all T cell subsets 15 . Although IL‐10 is considered to protect tissues from damage during inflammatory reactions, 16 overexpression of IL‐10 reportedly increased the pathogen burden and exacerbation of infection 17 . A previous study reported that neutralization of IL‐10 may lead to better control of tuberculosis 18 .…”
Section: Discussionmentioning
confidence: 99%